The novel psychoactive substance methoxetamine induces persistent behavioral abnormalities and neurotoxicity in rats. (January 2019) - Costa, Giulia; Serra, Marcello; Pintori, Nicholas; Casu, Maria Antonietta; Zanda, Mary Tresa; Murtas, Daniela; De Luca, Maria Antonietta; Simola, Nicola; Fattore, Liana
Abstract: Methoxetamine (MXE) is a novel psychoactive substance that can induce several short-term effects on emotional states and behavior. However, little is known about the persistent emotional and behavioral effects of MXE. Moreover, neurotoxic effects of MXE have been hypothesized, but never demonstrated in vivo . To clarify these issues, rats received repeated treatment with MXE every other day (0.1–0.5 mg/kg, i.p., × 5), and 7 days later they were challenged with MXE (0.1–0.5 mg/kg, i.p.). Behavioral effects of MXE were first evaluated by measuring emission of ultrasonic vocalizations and locomotor activity after each administration. Thereafter, persistent behavioral effects of MXE were evaluated, starting 8 days after challenge, through elevated plus maze, spontaneous alternation, novel object recognition, and marble burying tests. After completion of behavioral analysis, neurotoxic effects of MXE were evaluated by measuring densities of dopamine transporter, tyrosine hydroxylase, and serotonin transporter in various brain regions. Repeated treatment and challenge with MXE affected neither calling behavior nor locomotor activity of rats. Conversely, rats previously treated with MXE exhibited behavioral alterations in the elevated plus maze, marble burying and novel object recognition tests, suggestive of increased anxiety and impaired non-spatial memory. Noteworthy, the same rats displayed dopaminergic damage in the medial prefrontal cortex, nucleus accumbens, caudate-putamen, substantia nigra pars compacta, and ventral tegmental area, along with accumbal serotonergic damage. Our findings show for the first time that repeated administration of MXE induces persistent behavioral abnormalities and neurotoxicity in rats, which can help elucidating the risks associated with human MXE consumption. Graphical abstract: Image 1 Highlights: Methoxetamine is a novel psychoactive substance used as recreational drug. Little is known about the enduring effects of methoxetamine. We evaluated behavior and neurotoxicity in rats repeatedly exposed to methoxetamine. Methoxetamine induced persitent changes in emotional state and non-spatial memory. Methoxetamine persistently damaged the mesocorticolimbic dopaminergic system.